Walter L. Fisher papers - Fisher, Walter L. (Walter Lowrie), 1862-1935.
Correspondence, memoranda, letterbooks, minutes, speeches, articles, notes, subject files, Fisher family genealogical material, newspaper clippings, printed matter, scrapbooks, photographs, and other papers relating chiefly to Fisher's service as U.S. secretary of the interior in the William H. Taft administration and to his interest in the municipal affairs of Chicago, Ill. Also documents his work as a member of the U.S. Railroad Securities Commission. Subjects include the American National Live Stock Association; conservation; the Indians of Oklahoma; Sigma Chi fraternity; the League to Enforce Peace (U.S.); the traction ordinances dispute, Chicago, Ill.; Fisher's travels to Alaska, Hawaii, and Idaho; and personal matters. Correspondents include Richard Achilles Ballinger, Kate Barnard, Louis Dembitz Brandeis, James Rudolph Garfield, William Kent, Robert M. La Follette, Franklin K. Lane, Franklin MacVeagh, Frank B. Noyes, Gifford Pinchot, Julius Rosenwald, Harry Slattery, William H. Taft, Ida M. Tarbell, Henry Cantwell Wallace, George W. Wickersham, and Clinton Rogers Woodruff.
Lawyer, municipal reformer, and U.S. secretary of the interior.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ballinger, Richard Achilles, -- 1858-1922 -- Correspondence; Barnard, Kate, -- 1875-1930 -- Correspondence; Brandeis, Louis Dembitz, -- 1856-1941 -- Correspondence; Garfield, James Rudolph, -- 1865-1950 -- Correspondence; Kent, William, -- 1864-1928 -- Correspondence; La Follette, Robert M. -- 1855-1925 -- Correspondence; Lane, Franklin K. -- Correspondence; MacVeagh, Franklin, -- 1837-1934 -- Correspondence; Noyes, Frank B. -- 1863-1948 -- Correspondence; Pinchot, Gifford, -- 1865-1946 -- Correspondence; Rosenwald, Julius, -- 1862-1932 -- Correspondence; Slattery, Harry, -- 1887-1949 -- Correspondence; Taft, William H. -- 1857-1930.; Taft, William H. -- 1857-1930 -- Correspondence; Tarbell, Ida M. -- 1857-1944 -- Correspondence; Wallace, Henry Cantwell, -- 1866-1924 -- Correspondence; Wickersham, George W. -- 1858-1936 -- Correspondence; Woodruff, Clinton Rogers, -- 1868-1948 -- Correspondence; Fisher family; United States. -- Department of the Interior; United States. -- Railroad Securities Commission; American National Live Stock Association; League to Enforce Peace (U.S.); Sigma Chi Fraternity; Conservation of natural resources; Environmental policy -- United States; Genealogy; Greek letter societies; Indians of North America -- Oklahoma; International cooperation; Land use -- United States; Livestock -- United States -- Societies, etc; Local transit -- Illinois -- Chicago; Natural resources -- United States; Peace -- Societies, etc; Railroads -- United States; Alaska -- Description and travel; Chicago (Ill.) -- Politics and government -- To 1950.; Hawaii -- Description and travel; Idaho -- Description and travel; Cabinet officers; Lawyers; Reformers